Transfer of learning Selwasa Language in informal education in Marantutul Village, Tanimbar Islands Regency - Dian Wahyu P Soemarsono; Deby Marlina Kewilaa (Goodwood Publishing, 2025)
Purpose: This study examines strategies for transferring the Selwasa language through informal education in Marantutul Village. Research methodology: Data were obtained via interviews and observations, using descriptive qualitative analysis. Results: Selwasa is transmitted informally by parents and the community through everyday communication. Strategies include direct pronunciation, vocabulary instruction, reading, and sentence building. Children are encouraged to note new words and express themselves creatively through poetry, short stories, and group discussions. Two main strategies are identified: direct strategies (e.g., memory-based learning, daily language use) and indirect strategies (e.g., traditional games, storytelling, creative writing, discussions). Conclusions: The preservation of Selwasa in Marantutul Village relies on informal educational practices involving both direct and indirect strategies. These include vocabulary teaching, use in conversations, and participation in cultural activities. Such efforts not only pass on the language but also build emotional connections, helping reframe Selwasa as part of daily life rather than solely ritual use. This study offers insight into grassroots language revitalization in a multilingual context. Limitations: The study is limited to Marantutul Village, where Selwasa use is declining due to a shift toward Ambonese Malay and a weakening sense of linguistic identity. Contribution: The research documents community-based efforts to preserve and revitalize Selwasa through informal means. Novelty: While once limited to rituals, Selwasa is now taught as a living language for daily use among younger generations.